Effects of Geomagnetic Disturbances on Incidence ofStroke: Identifying Gaps for Future Research - Shamyar, S.; Yeghikyan, A.
Geomagnetic disturbances (GMDs)—transient variations in Earth’s magnetic field driven by solar activity—have garnered increasing attention for their potential impact on cardiovascular and cerebrovascular outcomes, including stroke. A growing body of epidemiological research has documented the correlations between geomagnetic storms and stroke incidence, particularly among high-risk populations. However, mechanistic studies remain scarce and existing findings are often inconsistent across geographic regions, stroke subtypes, and patient-specific variables. This paper presents a comprehensive review of the literature on GMDs and cerebrovascular health, highlights the physiological pathways that potentially link GMDs to stroke, and identifies key gaps in current research. We propose future interdisciplinary directions for integrating space weather forecasting with clinical neurology to inform early-warning systems and stroke prevention strategies.
Keywords: Аutonomic nervous system